Leadership Styles and Leadership Behaviors in Family Firms: A Systematic Literature Review. Issue 1 (March 2021) - Fries, Alexander; Kammerlander, Nadine; Leitterstorf, Max
Highlights: We conducted a systematic review of academic literature on leadership styles in family firms and we link generic leadership styles and family firm-specific leadership behavior. We developed a research model that categorizes the identified literature into antecedents and outcomes of leadership styles. Antecedents are categorized into family complexity, business complexity, and CEO attributes. Outcomes are categorized into family success, business success, leadership succession, and employee satisfaction. Future research needs to incorporate a broader range of theories to better theorize on leadership in family firms. ABSTRACT: Family firms are characterized by specific leadership settings that have recently attracted increasing scholarly attention. This study provides a systematic review of the academic literature on leadership in family firms. The systematic search process resulted in 99 relevant articles that were published in 25 different peer-reviewed journals. Based on our review, we contrast and integrate generic leadership styles, originating from the general leadership literature, with family firm-specific leadership behaviors . Moreover, we develop a framework that categorizes the identified literature and outlines specific antecedents as well as outcomes of leadership styles and behaviors in family firms. Finally, we discuss fruitful avenues for future research.